The Effect of Changes in Forest Area on the Transcarpathian Tisza River Basin - Szuhányi, György (Acta Agraria Debreceniensis, 2004)
Forests are unique global factors which ensure life for almost every living being on Earth. They play a major role in controlling water flows, preventing erosion and controlling the oxygen content of Earth’s atmosphere. By the end of the XXth century, it was realized that forests help to nature maintain and are vital parts of our natural environment. By the time societies realized this fact, economic and environmental effects had amplified which endanger forests. Due to their good water control and water protection abilities, and their function in climate control, mountain forests can provide a suitable environment for themselves, for their successful growth. Forests play a major role in soil protection, especially in mountain areas where they prevent soil erosion. By converting surface waters into subsurface waters, forests help with the accumulation of subsurface waters, which are the sources of springs, rivers and streams. In the summer, they protect the soil from drying out by creating a special microclimate. They positively affect the climate of surrounding territories.